Comprehensive analysis of nanodiamond evidence relating to the Younger Dryas Impact Hypothesis. (19th December 2016) - Daulton, Tyrone L.; Amari, Sachiko; Scott, Andrew C.; Hardiman, Mark; Pinter, Nicholas; Anderson, R. Scott
ABSTRACT: During the end of the last glacial period in the Northern Hemisphere near 12.9k cal a BP, deglacial warming of the Bølling–Ållerod interstadial ceased abruptly and the climate returned to glacial conditions for an interval of about 1300 years known as the Younger Dryas stadial. The Younger Dryas Impact Hypothesis proposes that the onset of the Younger Dryas climate reversal, Pleistocene megafaunal extinctions and disappearance of the Clovis paleoindian lithic technology were coeval and caused by continent‐wide catastrophic effects of impact/bolide events in North America. While there are no known impact structures dated to the Younger Dryas onset, physical evidence of the impact/bolide events is argued to be present in sediments spanning several continents at stratigraphic levels inferred to date to the Bølling‐Ållerod/Younger Dryas boundary (YDB). Reports of nanometer to submicron‐sized diamonds in YDB sediments, in particular the rare 2H hexagonal polytype of diamond, lonsdaleite, have been presented as strong evidence for shock processing of crustal materials. We review the available data on diamonds in sediments and provide new data. We find no evidence for lonsdaleite in YDB sediments and find no evidence of a spike in nanodiamond concentration at the YDB layer to support the impact hypothesis.